The development of the adult nervous system in the annelid Owenia fusiformis - Carrillo-Baltodano, Allan M.; Donnellan, Rory D.; Williams, Elizabeth A.; Jékely, Gáspár; Martín-Durán, José M. (Neural development, 2024)
The evolutionary origins of animal nervous systems remain contentious because we still have a limited understanding of neural development in most major animal clades. Annelids — a species-rich group with centralised nervous systems — have played central roles in hypotheses about the origins of animal nervous systems. However, most studies have focused on adults of deeply nested species in the annelid tree. Recently, Owenia fusiformis has emerged as an informative species to reconstruct ancestral traits in Annelida, given its phylogenetic position within the sister clade to all remaining annelids.
Gesehen am 27.02.2025
Illustrationen